Superconducting optical response of photodoped Mott insulators - Li, Jiajun; Golez, D.; Werner, P.; Eckstein, Martin (Modern Physics Letters B, 2020)
Ultrafast laser pulses can redistribute charges in Mott insulators on extremely short time scales, leading to the fast generation of photocarriers. It has recently been demonstrated that these photocarriers can form a novel η-paired condensate at low temperatures, featuring a staggered superconducting pairing field. In this conference paper, we discuss the origin of the η-paired hidden phase and its optical response, which may be detected in a pump-probe experiment. The hidden phase may be relevant for possible light-induced superconductivity in Mott insulators.
CRIS-Team Scopus Importer:2020-07-10
Keywords: Mott insulators; photocarriers; Superconducting optical response; ultrafast laser techniques